ð˜ð˜¯ ð˜·ð˜ªð˜µð˜³ð˜° SCREENING OF SUGARCANE (ð˜šð˜¢ð˜¤ð˜¤ð˜©ð˜¢ð˜³ð˜¶ð˜® ð˜°ð˜§ð˜§ð˜ªð˜¤ð˜ªð˜¯ð˜¢ð˜³ð˜¶ð˜® Linnaeus) ASSOCIATED RHIZOBACTERIA TO PLANT GROWTH PROMOTION - Montaldo, Yamina Coentro; Silva, JoÃ£o Manoel da; Silva, Paula Cibelly Vilela da; Almeida, Arthur Costa Pereira Santiago de; Costa, Jakes Halan de Queiroz; Santos, Tania Marta Carvalho dos (REVISTA DE AGRICULTURA, 2021)
The aimed of this study was to test in vitro four bacterial isolates (Bacillus megaterium, B. subtilis, B. pumilus, and Enterobacter cloaceae) with potential to plant growth promotion. The bacterial isolates were subjected to inorganic phosphate solubilization assay in liquid medium, exopolisacarÃdeos production and production of indole acetic acid (IAA) in vitro. The phosphorus solubilizing assay showed that B. megaterium is able to solubilizing phosphorus. Exopolysaccharides production test detected that B. megaterium and E. cloaceae are most efficient, and carbon source and pH were not dependent factors. The IAA production showed efficiency by E. cloaceae. These results proposed that bacterial isolates used in this study are applicable to inoculant production program and agricultural applicability.